Developmental Care For Physiological Stabilization In Low Birth Weight Infants With Mild Asphyxia From Mothers With Pulmonary Tuberculosis - Azzahra, Shafira; Hendrawati, Sri; Maryam, Nenden Nur Asriyani (CV. Utami, 2026)
Low birth weight (LBW) and neonatal asphyxia are major contributors to neonatal morbidity and mortality. Maternal factors such as active pulmonary tuberculosis may further worsen neonatal conditions through impaired intrauterine oxygenation, placing infants at high risk and requiring intensive physiological stabilization from the early neonatal period. Developmental care is a non-pharmacological intervention based on evidence-based practice that focuses on environmental regulation and stimulation tailored to the infant’s developmental needs. This case study aimed to describe the implementation of developmental care on physiological stabilization in a low birth weight infant with mild asphyxia born to a mother with active pulmonary tuberculosis. The study employed a case study design involving a one-day-old male neonate treated in a level II perinatology unit of a provincial referral hospital. The intervention was conducted over four days and included environmental modification, reduction of noise and lighting, use of nesting, implementation of clustered care, and maternal involvement through education and auditory stimulation. Physiological parameters observed included body temperature, respiratory rate, heart rate, oxygen saturation, sucking reflex, sleep patterns, level of calmness, and weight changes. The results demonstrated improved physiological stabilization, as indicated by vital signs within normal ranges, enhanced sucking reflex, improved sleep quality, and weight gain. Developmental care has the potential to support physiological adaptation and is recommended as an evidence-based neonatal nursing practice.